Fragmentation analyses of rocks under high-velocity impacts using the combined finite-discrete element simulation - Yang, Tao; Ma, Hui; Weng, Lei; Liu, Yang; Chu, Zhaofei; Zhang, Penglin; Jin, Gang; Chang, Weixue (Frontiers in Earth Science, 2022)
The impact-induced fragmentation of rock blocks is frequently encountered when the natural hazards (e.g., rockfalls, rockslides, and rock avalanches) occur in mountainous areas. To address the progressive damage and cracking characteristics of rock upon impacting, this paper presents a three-dimensional finite-discrete method (3D-FDEM) study on the complex impact-induced fragmentation process of rock. The influences of the impact velocity on the dynamic fragmentation process, damage evolution, fragment characteristics, fragment flying velocity, and angle were systematically investigated. The parameters as input for simulation were first calibrated by the 3D uniaxial compression tests and rock-impact tests. Then, the complex fragmentation process of rock samples subjected to different impact velocities (i.e., 20–80 m/s) was simulated. The numerical results show that the number of cohesive elements following shear-dominated failures gradually increases with increasing the impact velocity. The fractal method can well describe the distribution of the equivalent fragment length, and the variations of the fractal dimension are consistent with that of the damage ratio, increasing with impact velocity. Both the average and maximum flying velocities of the fragments increase linearly with increasing impact velocity. However, the average flying angle of the fragments shows a sharp increase and then slight increase with increasing the impact velocity.